Parenting and Psychological Health in Youth with Type 1 Diabetes: Systematic Review. (27th July 2021) - Trojanowski, Paige J; Niehaus, Claire E; Fischer, Sarah; Mehlenbeck, Robyn
Abstract: Objective: Type 1 diabetes (T1D) is a demanding chronic illness that may result in poorer psychological health in youth. Fortunately, certain parenting practices may be protective against adverse outcomes. However, a systematic review of these relationships in youth with T1D is lacking. Thus, the current systematic review examined the literature on parenting and child psychological health outcomes (both internalizing and externalizing symptoms) in youth with T1D. Particular attention is paid to how demographic factors are associated with these relationships. Methods: PRISMA guidelines for systematic reviews were followed, and a literature search (PubMed, PsycINFO, and CINAHL) was conducted for studies of youth with T1D that examined the relationship between specific parenting practices or characteristics of the parent–child relationship and youth (<19 years old) internalizing or externalizing symptoms. Forty studies met inclusion criteria. Studies were examined for risk of bias. Results: Results support that family conflict, critical parenting, support, involvement, and relationship quality are associated with psychological health outcomes in youth with T1D, with some associations varying by parent gender, child age, demographic factors, and internalizing versus externalizing outcomes. Conclusions: Findings highlight the importance of bolstering supportive parenting and decreasing family conflict to improve psychological health in this population. Gaps in the literature related to the dearth of father and secondary caregiver report, lack of sample diversity and attention to the influence of demographic factors, and a limited number of studies examining anxiety were identified. Directions for future research and clinical implications are discussed.